The role of portrait in Iranian cinema posters design - Keshavarzi, Firouzeh; Mohd Adnan, Hamedi (Elsevier Ltd., 2014)
One of the strongest methods used in sending messages in advertisement is to apply a portrait in graphic design, especially when we are addressing a large crowd of ordinary people.Since any advertisement is done thoughtfully and with a certain goal in mind, the portrait can be considered as an element in advertising.The art of graphic is known as a means of communication and media for a long time and its strong capabilities and effectiveness are globally recognized on issues, namely social, cultural, political and economic, etc. The art of portrait can be used as a cultural symbol in advertising